Isolation and Identification of Chitin and Chitosan Horseshoe Crab Shrimp Shell Using Infrared Spectroscopy - Barroroh, Himmatul; Nur Rizkiyah Rifai, Dewi; Jannah, Akyunul (International Journal of Engineering and Technology, 2019)
Isolation and identification of chitin and chitosan Horseshoe Crab Shrimp Shell has been carried out. There were several reports about chitin isolation on crabs and shrimp shells with different reagent concentrations due to the shell hardness difference. Mechanically, the Horseshoe Crab Shrimp Shell was harder than the two. The characterization of chitin and chitosan is implemented through Infra Red Spectroscopy. Isolation method consists of three steps. First, it was deproteination with various NaOH concentrations of 3.5%, 4.5%, 5.5%, 6.5% and 7.5%. The second was demineralization with various HCl concentrations of 1 M, 1.5 M, 2 M, 2.5 M, and 3 M. The two steps would produce chitin. The third step was deacetylation with a NaOH concentration of 50% to produce chitosan. The results showed that the optimum concentration of NaOH in deproteination step is 4.5% with the optimum concentration of released protein by 601 ppm. In addition, the optimum concentration of HCl in the demineralization step was 2.5 M with remaining ash in the chitin of 0,972%. Moreover, deacetylation degree (D%) of chitin and chitosan were 45.4% and 50.5% respectively. Infrared spectroscopy showed that secondary NH amide stretching of chitin was vanished on chitosan. Meanwhile, secondary C=O amide stretching shifted in chitin and disappeared on chitosan due to deasetylation.Â Â